“Panteões”, “cultura” e “história” em um domínio de atuação da “elite maranhense”: a revista IHGM - GARCES, Karolline Cristine Reis (2021)
This dissertation is part of a research agenda developed within the scope of the Laboratory of Studies on Political and Cultural Elites (LEEPOC) on the interpreters of Maranhão's "culture" and "history". To this end, it takes as source a publication from the Historical and Geographic Institute of Maranhão: the IHGM Magazine. A set of 45 issues published were analyzed and, based on this, the agents who stood out for signing a significant number of articles and identifying the privileged themes in the journal were located. We sought to understand, thus, the changes that occurred during the different phases of the publication, with regard to the social, cultural and political profiles of the main collaborators, as well as the subjects addressed by the authors of the texts.